Artesunate Inhibits Metastatic Potential in Cisplatin-Resistant Bladder Cancer Cells by Altering Integrins - Olesya Vakhrusheva; Fuguang Zhao; Sascha Dennis Markowitsch; Kimberly Sue Slade; Maximilian Peter Brandt; Igor Tsaur; Jindrich Cinatl; Martin Michaelis; Thomas Efferth; Roman Alexander Blaheta; Axel Haferkamp; Eva Juengel (Cells)
The survival of patients with locally advanced and metastatic bladder cancer (BCa) is persistently low. Hence, new treatment options are urgently needed. Artesunate (ART) a derivative of artemisinin, used in Traditional Chinese Medicine, shows anti-tumor activity extending over a broad spectrum of human cancers. As we have previously shown, ART inhibits growth in cisplatin-sensitive (parental) and cisplatin-resistant BCa cells. However, how ART acts on the metastatic potential of BCa remained unclear. To clarify, we applied ART to parental and cisplatin-resistant RT4, RT112, T24, and TCCSup BCa cell lines. We examined tumor cell adhesion to vascular endothelium and immobilized collagen and evaluated chemotactic activity, migration, and invasive activity of the BCa cells. Adhesion receptors, integrin α and β subtypes, integrin-linked kinase (ILK), and focal adhesion kinase (FAK) were investigated. The functional relevance of integrin expression altered by ART was determined by blocking studies. ART significantly reduced tumor cell adhesion to vascular endothelium and immobilized collagen in parental as well as in cisplatin-resistant BCa cells. Depending on cell type, ART suppressed tumor cell motility and diminished integrin expression (surface and total). Functional blocking of integrins altered by ART reduced cell adhesion and invasion of the BCa cells. Thus, the metastatic potential of parental and cisplatin-resistant BCa cells was significantly inhibited by ART, making it a promising treatment option for patients with advanced or therapy-resistant BCa.